Tea polyphenol EGCG inhibited colorectal-cancer-cell proliferation and migration via downregulation of STAT3 . (3rd December 2020) - Luo, Ke-Wang; Xia, Jun; Cheng, Bao-Hui; Gao, Han-Chao; Fu, Li-Wu; Luo, Xin-Le
Abstract: Background: Green tea is a popular beverage worldwide and epigallocatechin-3-gallate (EGCG) is the most bioactive polyphenol in green tea. Our study aims to investigate the anti-proliferation and anti-migration effects of EGCG against colorectal-cancer SW480, SW620, and LS411N cells, and elucidate the underlying mechanism. Methods: The in vitro anti-proliferation and anti-migration effects of EGCG against colon-cancer cells were evaluated using MTT, scratch-wound-healing, and transwell-migration assays. The effects of EGCG on apoptosis were assessed by Annexin V-FITC/PI double staining and JC-1 staining. Besides, Western blotting was employed to detect the protein-expression level and elucidate the underlying pathways. Real-time qPCR and dual-luciferase reporter assay were adopted to determine the mRNA level and promoter activity. Results: Our results demonstrated that treatment with EGCG resulted in significant inhibition of cell proliferation by the induction of apoptosis. EGCG also inhibited SW480 cell migration in a dose-dependent manner as assessed by wound-healing and transwell-migration assays. Western blot confirmed that EGCG induced apoptosis by the activation of Caspase-3 and PARP. In addition, both STAT3 and phosphorylated STAT3 (p-STAT3) were downregulated significantly by EGCG in three selected colorectal-cancer cell lines. EGCG treatment also resulted in a significant decrease in Bcl-2, MCL-1, and Vimentin, and an increase in E-cadherin. When STAT3 was inhibited, EGCG showed no obvious effect on cell proliferation and migration. Further investigation by luciferase-reporter-activity assay showed that EGCG suppressed the promoter activity of STAT3 and downregulated the transcription of STAT3. Conclusion: Our study presents evidence on the anti-proliferation and anti-migration effects of EGCG against colorectal-cancer SW480, SW620, and LS411N cells by downregulating the expression of STAT3 and suggests that EGCG could be an effective and natural supplement for colon-cancer treatment.